Reading a paper about eta invariants I came across a zeta-like function.

I'm looking for the analytic continuation of $$\sum_{k=1}^\infty k(k+a)^{-s}$$ at $s=0$, where $a$ is positive.

In the paper he just says "The [...] term causes no problem and at $s=0$ has the value $\left[\frac{(4a^2-1)}{12}\right]$." Unfortunately, I really don't see the that.

My first approach so far; I tried a Taylor series at $s=3$: \begin{align} \sum_{k=1}^\infty k(k+a)^{-s} &= \sum_{k=1}^\infty k \sum_{l=0}^\infty (-1)^l \begin{pmatrix}2+l \\ l\end{pmatrix} (k+a)^{-3-l} (s-3)^{l} \end{align} and inserted $s=0$ $$\sum_{k=1}^\infty \frac{k}{(k+a)^3} \sum_{l=0}^\infty \begin{pmatrix}2+l \\ l\end{pmatrix} \left( \frac{3}{k+a} \right)^l$$ which is for $a\geq 3$ $$ \sum_{k=1}^\infty \frac{k}{(k+a-3)^3}~. $$ That seems to converge if I didn't miscalculate. But what are the further steps in order to get the result above? Or is there a more skilful approach?

Thanks in advance!

  • $\begingroup$ Write $k=(k+a)-a$ and use Hurwitz zeta. $\endgroup$
    – efs
    Sep 1, 2018 at 11:04
  • $\begingroup$ There appears a $\zeta(1-s,a)$ which is not finite at $s=0$. :-/ $\endgroup$
    – YoungMath
    Sep 1, 2018 at 11:23
  • $\begingroup$ @YoungMath: It might help us if you gave a link to the paper, if it is in electronic form. $\endgroup$
    – Alex M.
    Sep 1, 2018 at 14:26
  • $\begingroup$ Of course. Linked it. It's on page 34. $\endgroup$
    – YoungMath
    Sep 1, 2018 at 14:40
  • $\begingroup$ No, it appears a $\zeta(s-1,a)$ at $s=0$. $\endgroup$
    – efs
    Sep 1, 2018 at 15:25

1 Answer 1


Let $a>0$. We can write $$f(s,a):=\sum_{k=1}^\infty k(k+a)^{-s}=\sum_{k=0}^\infty (k+a)^{-s+1}-a\sum_{k=0}^\infty (k+a)^{-s}=\zeta(s-1,a)-a\zeta(s,a).$$ Hence, $f$ has a meromorphic continuation to $\mathbb{C}$ with simple poles at $s=1$ and $s=2$.

Now, if $s=-n$ is a non-positive integer, it is known that $$\zeta(-n,a)=-\frac{B_{n+1}(a)}{n+1}$$ where $B_n(X)$ is the $n$-th Bernoulli polynomial. Hence, $$f(0,a)=\zeta(-1,a)-a\zeta(0,a)=-\frac{B_{2}(a)}{2}+aB_1(a).$$ Since $B_1(X)=X-1/2$ and $B_2(X)=X^2-X+1/6$, we obtain that $$f(0,a)=-\frac{6a^2-6a+1}{12}+a\frac{2a-1}{2}=\frac{6a^2-1}{12},$$ (unless I made some stupid mistake which I don't have the time to fix now).

  • $\begingroup$ Thank you for that concise and precise answer. Unfortunately that is not the result as in the paper. Putting $a=\frac{\lambda^2}{2}$ and multiply by a factor 2 should give the value noted in the paper but it doesn't. Although, I came to the same computation and so does WolframAlpha. Did I miss something silly? $\endgroup$
    – YoungMath
    Sep 1, 2018 at 21:32
  • $\begingroup$ That is why I wrote that I may have done a mistake, but I do not see where. $\endgroup$
    – efs
    Sep 1, 2018 at 21:46
  • $\begingroup$ Me neither. Seems perfectly right. I will calculate the second term and maybe in the end they fit together properly. Must be so since the final result equals half the A-genus. $\endgroup$
    – YoungMath
    Sep 1, 2018 at 22:06
  • $\begingroup$ Ok. Please tell me then the reason of why the different results. Maybe a misprint? $\endgroup$
    – efs
    Sep 1, 2018 at 22:18
  • $\begingroup$ The final result actually fits. Apparently it's a misprint. $\endgroup$
    – YoungMath
    Sep 12, 2018 at 14:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.